Perkembangan Pendidikan Indonesia Pada Zaman Penjajahan II - Alfarizi, Raffi Dian; Sholekhah, Kurnia Alfi; Kusmawati, Heny Kusmawati (Educationist: Journal of Educational and Cultural Studies, 2023)
Education as one of the precepts in Ethical Politics, enabling the Indonesian people to experience formal education, like other nations. This paper aims to explain how the development of education in Indonesia during the colonial era II. This study uses historical research methods. In the early 20th century Indonesia used an ethical political system in education. Ethical politics for the Indonesian nation has a very important influence in the effort to win independence. Then in the period before the entry of Japan, the Dutch Colonial first entered Indonesia at the end of the 16th century, the first school in Ambon was founded by the VOC in 1607. The lessons provided were reading, writing and praying. In 1617 the first school was founded in Jakarta. Then the development of national education in the early 20th century Ki Hajar Dewantara founded Taman Siswa as a concrete manifestation of his words that education is a tool to fight for culture. Since its inception, Taman Siswa has carried the vision of educating the nation's life, departing from criticism of the schools established by the Dutch colonialists which only facilitated the sons and daughters of aristocrats. Then, the existence of education organized by the government in the form of state schools made several people's education foundations also organize educational programs in the form of private schools. Private schools are recorded as colonial education in Indonesia. Then in 1912 Kyai Haji Ahmad Dahlan founded the Muhammadiyah Organization, but before the official establishment of Muhammadiyah, the Madrasah Ibtidaiyah Diniyah Islamiyah school had already been established. In 1942 the pacific war began; Japan dominated the course of the war. The Dutch government in power in Indonesia (Dutch East Indies) surrendered unconditionally to the Japanese in 1942. To gain the sympathy of the Indonesian people, the Japanese leveled education in Indonesia. On the other hand, the Japanese government also increased physical training and shortened school study time to form an accumulation of volunteers. natives needed by the Japanese to gain victory in Greater East Asia.